Efeitos periféricos e centrais decorrentes da exposição à cocaína e testosterona em ratos adolescentes e adultos - Engi, Sheila Antonagi (Universidade Federal de São Carlos, 2012)
Drug abuse is considered a major public health problem in the world. The use of cocaine and anabolic-androgenic steroids (AAS) has increased in Brazil. Epidemiological studies indicate that adolescents are more vulnerable than adults to progress from the occasional use of drugs to dependence and that teenagers have a higher incidence of cocaine and testosterone abuse. There is evidence that testosterone can modify the acute effects of cocaine and increase dopaminergic transmission that could lead to behavioral cross-sensitization. Studies have shown that the use of cocaine or ASS promotes toxicity to the heart and liver. Thus, the purpose of the present study was to investigate: 1) whether the prior administration of AAS could cause cross-sensitization with cocaine and thereby increase the vulnerability to abuse and dependence to this psychostimulant, 2) the cardiovascular effects resulted from chronic use of these substances combined and 3) the toxic effects resulted from chronic use of these substances combined. In this way, our results showed that chronic administration of testosterone caused cross-sensitization to cocaine in adolescent, but not in adult rats. And that the combined chronic administration of testosterone and cocaine caused increased MAP, SAP and DAP in adult, but not in adolescent rats. Furthermore, our results showed that the chronic testosterone and cocaine administration caused no damages to liver cellules but caused severe damages to heart tissue in adolescent and adult rats.
Keywords: Fisiologia; Cocaína; Testosterona; Sensibilização central; Efeitos periféricos; Ratos; CIENCIAS BIOLOGICAS::FISIOLOGIA